Komunikasi Interpersonal Antara Koordinator Dan Anggota Pengelola Ruang Publik Terpadu Ramah Anak Kelurahan Galur Jakarta Pusat - Muhammad Septian; Angelika Rosma (LUGAS Jurnal Komunikasi, 2021)
Interpersonal communication between the coordinator and members has an important role in supporting performance, but conditions show that interpersonal communication between the implementers of the Galur Village RPTRA Manager still looks bad, this can be seen from the frequent misunderstandings in the process of carrying out tasks.  Thus, the research question can be formulated, namely how is Interpersonal Communication Between Coordinators and Members of the Child Friendly Integrated Public Space Management (RPTRA) Galur Village, Central Jakarta Administration, and the aim is to find out the Interpersonal Communication between the Coordinator and Members of the Child Friendly Integrated Public Space Management (RPTRA)  Galur Village, using descriptive qualitative research methods through observation and in-depth interviews with informants, namely the management members as the object of research.  The results of the study show: a), there is still weak or lack of communication between the coordinator and the management members so that they become passive in interacting, b) there are obstacles, namely the lack of discussion space and regular meetings.  The research suggestions to overcome the obstacles faced are by scheduling regular meetings, making capacity building/training training, increasing the capacity of members, and family gatherings to increase intimacy